Biallelic variants of ATP13A3 cause dose-dependent childhood-onset pulmonary arterial hypertension characterised by extreme morbidity and mortality. Issue 9 (7th September 2021) - Machado, Rajiv D; Welch, Carrie L; Haimel, Matthias; Bleda, Marta; Colglazier, Elizabeth; Coulson, John D; Debeljak, Marusa; Ekstein, Josef; Fineman, Jeffrey R; Golden, William Christopher; Griffin, Emily L; Hadinnapola, Charaka; et al.
Abstract : Background: The molecular genetic basis of pulmonary arterial hypertension (PAH) is heterogeneous, with at least 26 genes displaying putative evidence for disease causality. Heterozygous variants in the ATP13A3 gene were recently identified as a new cause of adult-onset PAH. However, the contribution of ATP13A3 risk alleles to child-onset PAH remains largely unexplored. Methods and results: We report three families with a novel, autosomal recessive form of childhood-onset PAH due to biallelic ATP13A3 variants. Disease onset ranged from birth to 2.5 years and was characterised by high mortality. Using genome sequencing of parent–offspring trios, we identified a homozygous missense variant in one case, which was subsequently confirmed to cosegregate with disease in an affected sibling. Independently, compound heterozygous variants in ATP13A3 were identified in two affected siblings and in an unrelated third family. The variants included three loss of function variants (two frameshift, one nonsense) and two highly conserved missense substitutions located in the catalytic phosphorylation domain. The children were largely refractory to treatment and four died in early childhood. All parents were heterozygous for the variants and asymptomatic. Conclusion: Our findings support biallelic predicted deleterious ATP13A3 variants in autosomal recessive, childhood-onset PAH, indicating likely semidominant dose-dependent inheritance for this gene.